Sistem Penjualan Kopi Gayo Pada Koperasi Baitul Qirad Berbasis Web - Seftiawan AY; T. Rafli Abdillah; Rizka Ramadhana (Jurnal Ilmu Komputer Aceh, 2025)
E-commerce no longer requires displaying goods or services to be offer to consumers in cabinets and stores. In this E-commerce, it could provide information about the products to be offer. Coffee has become one of the products which is highly demanded and sold online through e-commerce. This research focused on creating an e-commerce platform for the Baitul Qirad Baburayyan cooperative in selling coffee. The method used is web engineering, which consists of planning, analysis engineering, page generation, testing, and customer evaluation. The result of this research is an e-commerce platform that enables online purchases through the Baitul Qirad Baburayyan cooperative. This website assisted and facilitated both administrators and users in conducting online buying and selling transactions